2019
DOI: 10.1080/21507740.2019.1632972
|View full text |Cite
|
Sign up to set email alerts
|

The Need for a Conceptual Expansion of Neuroethics

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles design in nature prior to Darwin, so too naturalists have struggled to explain ethics without a unifying theory of morality. Perhaps the greatest contribution of neuroethics will be something like a Darwinian revolution for morality, and any reflection on the future work of neuroethics must emphasize the pursuit of this revolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…This is because neuroethics attempts to provide collective answers to ethical, legal and social implications of neuroscientific research [ 25 ]. Neuroethics overlaps with traditional biomedical ethics to a substantive level and all too often it is taken to be a subfield of applied ethics [ 26 ]. However, previous research has shown that neuroethical research is larger in scope and in methodological approaches and calls for a conceptual expansion of neuroethics to accommodate progress being made in neuroscience.…”
Section: Conceptsmentioning
confidence: 99%
“…This is because neuroethics attempts to provide collective answers to ethical, legal and social implications of neuroscientific research [ 25 ]. Neuroethics overlaps with traditional biomedical ethics to a substantive level and all too often it is taken to be a subfield of applied ethics [ 26 ]. However, previous research has shown that neuroethical research is larger in scope and in methodological approaches and calls for a conceptual expansion of neuroethics to accommodate progress being made in neuroscience.…”
Section: Conceptsmentioning
confidence: 99%
“…Through the efforts of the HBP, EBRAINS is intended to integrate neuroethics and philosophical analysis to enhance the neuroscientific work ( Evers, 2009 ; Salles et al, 2019a , b ). Philosophical analysis provides clarification of scientific concepts such as behavior, intelligence, digital twin and consciousness and explores how neuroscientific knowledge is constructed, what are its underlying assumptions and how they are justified, how results may be interpreted, and why or how empirical knowledge of the brain can be relevant to philosophical, social, and ethical concerns ( Pennartz, 2015 ; Salles et al, 2019b ).…”
Section: Collaborative Perspectivesmentioning
confidence: 99%
“…Fundamental neuroethics takes as a starting point the view that conceptual analysis plays an important role not only in illuminating key operative notions (e.g. consciousness, self, and human identity), but also in examining issues such as what is the understanding of the same notions in different contexts (i.e., ethics and neuroscience) and their mutual relevance, how neuroscientific knowledge is constructed, what its underlying assumptions are and how they are justified, how results may be interpreted, and why or how empirical knowledge of the brain can be relevant to philosophical, social, and ethical concerns [26,31,32].…”
Section: An Excursion Into Neuroethicsmentioning
confidence: 99%